2016
DOI: 10.18632/oncotarget.7880
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-linked kinase activity modulates the pro-metastatic behavior of ovarian cancer cells

Abstract: Epithelial ovarian cancer (EOC) is the most fatal gynecologic cancer in the U.S., resulting in >14,000 deaths/year. Most women are diagnosed at late stage with widely disseminated intra-peritoneal metastatic disease, resulting in a 5-year survival rate of <30%. EOCs spread via direct extension and exfoliation into the peritoneal cavity, adhesion to peritoneal mesothelial cells, mesothelial cell retraction to expose sub-mseothelial matrix and anchoring in the type I collagen-rich matrix to generate secondary le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 58 publications
3
24
0
Order By: Relevance
“…These data are consistent with previous results in which pharmacologic inhibition or genetic silencing of integrinlinked kinase (ILK) was used to prevent phosphorylation of Thr 567 in DOV13 cells, which endogenously express MT1-MMP (31). In this study, results observed were similar to those using cells transfected to exogenously express the phosphodefective mutant T567A in the current study.…”
Section: Mt1-mmp Thr 567 and Multicellular Aggregate Dynamicssupporting
confidence: 93%
See 2 more Smart Citations
“…These data are consistent with previous results in which pharmacologic inhibition or genetic silencing of integrinlinked kinase (ILK) was used to prevent phosphorylation of Thr 567 in DOV13 cells, which endogenously express MT1-MMP (31). In this study, results observed were similar to those using cells transfected to exogenously express the phosphodefective mutant T567A in the current study.…”
Section: Mt1-mmp Thr 567 and Multicellular Aggregate Dynamicssupporting
confidence: 93%
“…Ala for Thr) (30). Using this approach, phosphorylation of MT1-MMP at Thr 567 of the cytoplasmic tail has been shown to promote expansive growth of invasive tumor cell colonies within constrained three-dimensional collagen gels (22,23,31,32). To investigate further the potential role of MT1-MMP Thr 567 in cellular behaviors correlated with metastasis, GFP-tagged MT1-MMP phosphomimetic (T567E (TE)) and phosphodefective (T567A (TA)) mutants as well as wild-type MT1-MMP (MT) were expressed in OVCA433 cells, which have very low levels of endogenous MT1-MMP ( Fig.…”
Section: Expression Of Mt1-mmp Thr 567 Mutants Alters E-cadherin Intementioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ILK is expressed in ovarian cancers and ILK expression increases with ovarian cancer progression [2931]. ILK expression is an initial early event in EOC metastasis, which suggested that further evaluation of ILK inhibitors in EOC is warranted [32].…”
Section: Discussionmentioning
confidence: 99%
“…An example is the inhibition of ILK, an integrin‐linked kinase involved in AKT pathway activation leading to EMT (Jiang et al ., ). Treatment with emodin (1,3,8‐trihydroxy‐6‐methylanthraquinone) (Bruney et al ., ), promotes a MET process by targeting ILK in ovarian cancer (Lu et al ., ) and endometrial sarcoma cells (Zheng et al ., ), in addition to reducing EMT through the ILK/AKT/mTOR signaling pathway in breast cancer cells (Ma et al ., ) (Fig. ).…”
Section: Current Clinical Status Of Emtmentioning
confidence: 99%